(untitled) (Ágora de Heterodoxias, 2025)
The comprehensive well-being of workers in Mexican small and medium-sized companies (SMEs) has gained increasing relevance in recent years in terms of the implementation of work practices that promote positive work environments. This concern tends to align with the Sustainable Development Goals (SDGs), specifically SDG 3 (Health and Wellbeing) and SDG 8 (Decent Work and Economic Growth). The objective was to determine the degree of influence of SDGs 3 and 8 on the probability of occurrence in the comprehensive work well-being of employees in relation to the reduction of psychosocial risk factors in small and medium-sized companies. The study had a quantitative, cross-sectional, causal-predictive approach, using a binary logistic regression model. It is concluded that the generated model presented a predictive capacity of 71.7% in terms of adjustment of the prediction value where psychosocial factors are reduced only by SDG 3, which covers aspects related to positive affective states and well-being. physical and mental level of workers in small and medium-sized businesses in the Municipality of Hermosillo, Sonora, Mexico.